The Impact of Age-Related Marriage Impediment Norms on Engagement Practices in the Context of Religious Freedom - Jabłońska, Paulina (Prawo Kanoniczne, 2025)
The article examines the historical evolution of age-related impediment norms in Roman and canon law, exploring their impact on individual autonomy in choosing a partner for engagements and marriages within the context of freedom of conscience and religion. The study aims to demonstrate how these regulations have shaped individual freedom across various historical periods and their relevance to contemporary canon law. In ancient Rome, engagements (sponsalia) allowed only limited personal autonomy, operating under patriarchal control and reflecting aspects of religious freedom through rites associated with the cult of Juno. In the Middle Ages, Gratian’s Decretum established marital consent as the foundation of freedom of conscience, distinguishing between the consensual and the copulatory theories in defining the essence of marriage. The Council of Trent, through the Tametsi Decree, codified consent as a sacramental requirement, responding to Protestant rejection of sacramentality and reinforcing Catholic religious freedom in marriage. The analysis is based on historical-legal sources, including Roman texts, canonical documents, and decretist commentaries. The findings indicate that the evolution of age-related norms has shaped the modern understanding of marriage as an act of free will, reflected in the Code of Canon Law (can. 1083), which regulates the minimum marriage age.